Peranan Roh Kudus dalam Memberi Kekuatan bagi Orang Percaya Berdasarkan Efesus 3:16 - Theofilus Sunarto (Jurnal Teologi Berita Hidup, 2022)
AbstractPaul's prayer in Ephesians 3:16, "I pray that he, according to the riches of his glory, may be strengthened and strengthened with power through his Spirit in the inner man." The Epistle of Ephesians was written by Paul while in prison, Paul wanted to strengthen the believers in Ephesus, especially in his prayer 3: 14-21 so that they would be strengthened and strengthened so that the faith of Christ remains and is rooted in their lives of love. This is what is the discussion in this article, parsing this verse, knowing the role of the Holy Spirit in giving strength to believers. The role of the Holy Spirit is very important to believers, because human beings basically have shortcomings and weaknesses. By their own strength human beings are more often lost and unable to make a decision that comes with good. Man needs a power that exceeds his own power or even the supernatural power of the Holy Spirit. With the Holy Spirit the believer will gain the strength to strengthen his faith, as a foundation in the course of his life in the Lord Jesus Christ.Keywords: Holy Spirit; Believers; Ephesians 3:16AbstrakDoa Paulus dalam Efesus 3:16, “Aku berdoa supaya Ia, menurut kekayaan kemuliaan-Nya, menguatkan dan meneguhkan kamu oleh Roh-Nya di dalam batinmu”.  Surat Efesus di tulis Paulus waktu di penjara, Paulus ingin menguatkan orang percaya yang di Efesus, khususnya dalam doa-nya 3:14-21 supaya mereka diteguhkan dan dikuatkan sehingga iman Kristus tetap tinggal dan berakar dalam kehidupan kasih mereka. Inilah yang menjadi pembahasan dalam artikel ini, mengupas ayat ini, mengetahui peranan Roh Kudus dalam memberi kekuatan bagi orang percaya.  Peranan Roh Kudus sangat penting bagi orang percaya, karena manusia pada dasarnya mempunyai kekurangan dan kelemahan.  Dengan kekuatannya sendiri manusia lebih sering tersesat dan tidak mampu untuk memutuskan sebuah keputusan yang mendatangan kebaikan.  Manusia membutuhkan kekuatan yang melebihi kekuatan sendiri atau bahkan kekuatan supranatural yaitu Roh Kudus.  Dengan Roh Kudus orang percaya akan memperoleh kekuatan untuk meneguhkan iman-nya, sebagai landasar dalam perjalanan hidupnya di dalam Tuhan Yesus Kristus.Kata-kata kunci: Roh Kudus ; Orang Percaya; Efesus 3:16